Terrestrial laser scanning and structure-from-motion photogrammetry concordance analysis for describing the surface layer of gravel beds. (April 2019) - Neverman, Andrew J; Fuller, Ian C; Procter, Jon N; Death, Russell G
Terrestrial laser scanning (TLS) and structure-from-motion photogrammetry (SfMp) offer rapid, non-invasive surveying of in situ gravels. Numerous studies have used the point clouds derived from TLS or SfMp to quantify surface layer characteristics, but direct comparison of the methods for grain-scale analysis has received relatively little attention to date. Comparing equivalent products of different data capture methods is critical as differences in errors and sampling biases between the two methods may produce different outputs, effecting further analysis. The sampling biases and errors related to SfMp and TLS lead to differences in the point clouds produced by each method. The metrics derived from the point clouds are therefore likely to differ, potentially leading to different inputs for entrainment threshold models, different trends in surface layer development being identified and different trajectories for physical processes and habitat quality being predicted. This paper provides a direct comparison between TLS and SfMp surveys of an exposed gravel bar for three different survey periods following inundation and reworking of the bar surface during high flow events. The point clouds derived from the two methods are used to describe changes in the character of the surface layer between bar inundation events, and comparisons are made with descriptions derived from conventional pebble counts. The results found differences in the metrics derived using each method do exist, but the grid resolution used to detrend the surfaces and identify spatial variations in surface layer characteristics had a greater impact than survey method. Further research is required to understand the significance of these variations for quantifying surface texture and structure and for predicting entrainment thresholds and transport rates.